Sustaining brand loyalty: The moderating role of green consumption values. (15th April 2021) - Rizomyliotis, Ioannis; Poulis, Athanasios; Konstantoulaki, Kleopatra; Giovanis, Apostolos
Abstract: Environmental issues are massively emerging in the current agendas of governments, businesses and consumers all over the globe. Consumers increasingly adopt a more energetic role in the environmental discussion and employ product consumption to manifest their contribution to the debate. Equally, a growing number of businesses try to affect positive social change, whereas others strategically approach green opportunities; at the same time, they persistently intensify their branding offerings to sustain loyalty. This article brings into discussion green consumption values as the authors aim to shed light into the way the latter moderate the effect of brand related factors, namely, brand experiences and brand personality, on brand loyalty. Based on data received from 413 participants and using the wearable technologies industry as the focal context, the study underscores the significance of green consumption values. Findings are discussed, and implications for managers are provided.